2014
DOI: 10.1242/dev.112888
|View full text |Cite
|
Sign up to set email alerts
|

The zinc-finger protein basonuclin 2 is required for proper mitotic arrest, prevention of premature meiotic initiation and meiotic progression in mouse male germ cells

Abstract: Absence of mitosis and meiosis are distinguishing properties of male germ cells during late fetal and early neonatal periods. Repressors of male germ cell meiosis have been identified, but mitotic repressors are largely unknown, and no protein repressing both meiosis and mitosis is known. We demonstrate here that the zinc-finger protein BNC2 is present in male but not in female germ cells. In testis, BNC2 exists as several spliced isoforms and presumably binds to DNA. Within the male germ cell lineage, BNC2 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 56 publications
(58 reference statements)
2
22
0
2
Order By: Relevance
“…Demethylation of testis-specific genes may be required for meiotic initiation, since DNA methyltransferases are attenuated significantly in type B spermatogonia and preleptotene spermatocytes. Recently it has been reported that down-regulation of DNMT3L may increase the expression of the premeioticspecific gene-STRA8, leading to the onset of meiosis prematurely (Vanhoutteghem et al 2014). In addition, it has been revealed that 5mC-specific dioxygenase (TET1) can mediate the demethylation of the locus-specific genes, including the meiotic genes, and promotes the meiotic initiation through the activation of these genes in oocytes (Yamaguchi et al 2012).…”
Section: Dna Methylation and Ssc Division And Differentiationmentioning
confidence: 99%
“…Demethylation of testis-specific genes may be required for meiotic initiation, since DNA methyltransferases are attenuated significantly in type B spermatogonia and preleptotene spermatocytes. Recently it has been reported that down-regulation of DNMT3L may increase the expression of the premeioticspecific gene-STRA8, leading to the onset of meiosis prematurely (Vanhoutteghem et al 2014). In addition, it has been revealed that 5mC-specific dioxygenase (TET1) can mediate the demethylation of the locus-specific genes, including the meiotic genes, and promotes the meiotic initiation through the activation of these genes in oocytes (Yamaguchi et al 2012).…”
Section: Dna Methylation and Ssc Division And Differentiationmentioning
confidence: 99%
“…Abnormal gene expression during spermatogonial differentiation leads to either a spermatogenic arrest at a pre-meiotic stage or a precocious entry of meiosis. 3, 4 …”
mentioning
confidence: 99%
“…Для модельных объектов предложены кандидатные гены, экспрессирующие консервативный белок подавления митоза в мужских ПК во время про-должительного периода блока их пролиферации до по-лового созревания. Сперматогонии мышей при недо-статке белка базонуклеин 2 (bnc2) рано вступают в мейоз [12]. Консервативный белок bnc2 присутству-ет только в мужских ПК, останавливает митоз и бло-кирует мейоз, связываясь с ДНК.…”
Section: таблица 2 количественные характеристики состава соматическиunclassified
“…В настоящий момент информация о динамике пре-лептотенных преобразований в сперматогенезе фраг-ментарна [4,[11][12][13]. Эта стадия непосредственно следу-ет за последним синтезом ДНК перед началом мейоза.…”
unclassified